2023
DOI: 10.1371/journal.pgen.1010751
|View full text |Cite|
|
Sign up to set email alerts
|

Structural variation underlies functional diversity at methyl salicylate loci in tomato

Abstract: Methyl salicylate is an important inter- and intra-plant signaling molecule, but is deemed undesirable by humans when it accumulates to high levels in ripe fruits. Balancing the tradeoff between consumer satisfaction and overall plant health is challenging as the mechanisms regulating volatile levels have not yet been fully elucidated. In this study, we investigated the accumulation of methyl salicylate in ripe fruits of tomatoes that belong to the red-fruited clade. We determine the genetic diversity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The presence of missing marker loci can be attributed to various factors, including variations in primer sites and the potential presence of structural variations in the targeted regions. Structural variations, such as insertions, deletions, or duplications, can significantly impact gene expression and protein functions, leading to variations in phenotype ( Alonge et al., 2020 ; Sapkota et al., 2023 ). Therefore, the observed missing marker loci are possibly associated with the phenotypic natural variation observed in the species being evaluated, providing valuable insights into the underlying genomic variation contributing to the diverse phenotypes within the collection.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of missing marker loci can be attributed to various factors, including variations in primer sites and the potential presence of structural variations in the targeted regions. Structural variations, such as insertions, deletions, or duplications, can significantly impact gene expression and protein functions, leading to variations in phenotype ( Alonge et al., 2020 ; Sapkota et al., 2023 ). Therefore, the observed missing marker loci are possibly associated with the phenotypic natural variation observed in the species being evaluated, providing valuable insights into the underlying genomic variation contributing to the diverse phenotypes within the collection.…”
Section: Discussionmentioning
confidence: 99%
“…Genomics data may further advance tropical fruit flavour through targeted breeding and genetic selection strategies or gene-editing technology (Mathiazhagan et al 2021 ). Genome-wide association studies (GWAS) and quantitative trait loci (QTL) mapping approaches have previously identified genome regions responsible for the regulation of fruit flavour compounds in tomato (Gai et al 2023 ; Sapkota et al 2023 ), grape (Koyama et al 2022 ; Bosman et al 2023 ) and apple (Yang et al 2023 ).…”
Section: Introductionmentioning
confidence: 99%